2006
DOI: 10.4319/lo.2006.51.5.2278
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and nutrient supply interact to control nitrogen fixation in oligotrophic streams: An experimental examination

Abstract: We performed two experiments to examine how temperature and nutrients interact to control dinitrogen (N 2 ) fixation, chlorophyll a (Chl a) biomass, and community composition of periphyton in subalpine oligotrophic streams in the Sawtooth Mountains of Idaho. We grew periphyton on nutrient-diffusing substrata (NDS) in a cold lake inlet (7uC) and a warm lake outlet (18uC). We then switched substrata between the two stream sites to test the effect of incubation temperature on N 2 -fixation rates. Periphyton on su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
64
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 46 publications
10
64
1
3
Order By: Relevance
“…P enrichment also increased periphyton biomass (as chlorophyll a [CHLA]), but N enrichment had no effect on periphyton biomass. Therefore, the study by Marcarelli and Wurtsbaugh (2006) provided a good example of how N 2 fixation can supplement the N supply to periphyton communities that are strongly P limited. What remains unclear is how much N can be provided by N 2 fixation in streams experiencing stronger N limitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…P enrichment also increased periphyton biomass (as chlorophyll a [CHLA]), but N enrichment had no effect on periphyton biomass. Therefore, the study by Marcarelli and Wurtsbaugh (2006) provided a good example of how N 2 fixation can supplement the N supply to periphyton communities that are strongly P limited. What remains unclear is how much N can be provided by N 2 fixation in streams experiencing stronger N limitation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Grimm and Petrone (1997) demonstrated that fixed N 2 provided up to 85% of the net N flux into the benthos of a desert stream. Marcarelli and Wurtsbaugh (2006) recently showed that P and temperature interacted to control N 2 fixation in periphyton from oligotrophic streams. P enrichment increased periphyton N 2 fixation rates by increasing the density of N 2 -fixing organisms within the periphyton community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, other soil components have effects of the background value of nitrogen; for instance, the content of clay particles in soil could affect the mass fraction of TN in soil [35]. Meanwhile, those impacts mainly related to temperature [36]. However, in this study, TN was taken as the pollutant, which included various forms of nitrogen; therefore, the impacts of the conversion among various forms of nitrogen on TN concentrations and TN loads could be ignored.…”
Section: Experimental Devicesmentioning
confidence: 99%
“…In aquatic systems, BNF is most commonly carried out by cyanobacteria, and is highly seasonally and spatially variable (Marcarelli andWurtsbaugh 2009, Patoine et al 2006). N fixation typically peaks in late summer when inflows are lowest, light availability is greatest and water temperature is highest (Marcarelli and Wursbaugh 2009 while short-term sinks include N burial in sediment, and N uptake by primary producers.…”
Section: N Transport Through and Transformation Within Lentic Systemsmentioning
confidence: 99%